Scale elements for design elevations - McGarry, Richard M.; Madsen, Greg. (New York : Van Nostrand Reinhold Company, Inc., 1991)
This book was created to help make one specific type of graphic communication. your elevations, into a better sales tool to use with your client.
Introduction -- Techniques for using entourage -- People -- Vehicles -- Trees and shrubs -- Interior foliage -- Index.
Includes index.
Keywords: ENTOURAGE -- ARCHITECTURAL RENDERING